Analytical Study of Aluminum Alloy Based Liquid Helium Dewar Vessel: Investigation of Heat Leaks in Aluminum Alloy Based Liquid Helium Dewar Vessel (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The existing work compacts with 100 liter nominal capacity liquid He(helium) dewar that utilizes multi insulation system employing the cold from evaporated vapor of the hold on cryogenic liquid, the analytical investigation of aluminium alloy based liquid helium Dewar vessel. The work is administrated by estimating the heat leak apparatuses because of numerous origins like Heat leak through the neck tube by apparent solid conduction and fluid conduction that might be determined from the balance of the heat inputs to the liquid and vapor columns, funneling radiation heat leak from the neck high flange, radiation heat leak from the radiation shield, and heat leak by residual gas conduction within the vacuum area etc.